Effects of norms and policy incentives on household recycling. An international comparison - Bente Halvorsen (Statistics Norway, Research Department, 2010)
Increased household recycling is a policy goal in many countries. Household recycling is, to a large extent, based on voluntary efforts. It is thus interesting to understand the mechanisms behind household voluntary contributions to recycling, and how they are affected by various policy measures. In this study, we describe the differences in factors affecting household recycling activities across 10 OECD countries. We find that the most important motivations for household recycling are the belief that recycling is good for the environment and that recycling is a civic duty. Increasing the supply of recycling services has a significant effect on household recycling, and door-to-door collection and drop-off centres are the two most effective methods in this respect. Furthermore, the results indicate that the design of monetary incentives may be important to avoid crowding out of morally motivated voluntary contributions, illustrated by the Korean success with volume-based fees.
Keywords: C21; H42; 330; Household recycling; norms; international comparison